Virtual microscope interface to high resolution histological images - Feit, Josef; Matyska, Ludek; Ulman, Vladimír; Hejtmánek, Lukás; Jedlicková, Hana; Jezová, Marta; Moulis, Mojmír; Feitová, Vera (Diagnostic pathology, 2008)
The Hypertext Atlas of Dermatopathology, the Atlas of Fetal and Neonatal Pathology and Hypertext Atlas of Pathology (this one in Czech only) are available at http://www.muni.cz/atlases. These atlases offer many clinical, macroscopic and microscopic images, together with short introductory texts. Most of the images are annotated and arrows pointing to the important parts of the image can be activated.The Virtual Microscope interface is used for the access to the histological images obtained in high resolution using automated microscope and image stitching, possibly in more focusing planes. Parts of the image prepared in advance are downloaded on demand to save the memory of the user's computer. The virtual microscope is programmed in JavaScript only, works in Firefox/Mozilla and MSIE browsers without need to install any additional software.